Effects of Oil-Coated Pellets and Feeding Frequency on The Growth and Body Composition of Tilapia (Early view) - Chee Ping Tan, Wen Jye Mok, Mohamad Jalilah, Jeremiah Olanipekun Jimoh, Leong-Seng Lim; Hon Jung Liew (Tropical Life Sciences Research, 2026)
Fish oil with its proven health benefits is widely used for pharmaceutical purposes including aquaculture industry, nevertheless, excess intake may result in health alteration. This study investigated the effect of fish oil supplementation on growth and body composition of juvenile tilapia. The control group received only grain pellets containing 3% crude lipid, while the treatment groups received fish oil supplementation at 5 and 7% of crude lipid. Each treatment was fed at a frequency of 2 and 4 times per day for five weeks. Results showed that 7% lipid supplementation shown the best relative weight gain under the 4 times feeding frequency, while the relative weight gain across the various lipid supplementation in the 2 times feeding frequency were not significantly different. There was no observed significant difference in the lipid composition of the muscle across the treatments indicated that there was no lipid deposition in the muscle despite the increase in the oil coating. Furthermore, the lipid levels in the livers of all tilapia fed 5 and 7% dietary lipid were significantly higher than those of the control groups. Fatty acids composition did not show many remarkable differences between control and treatment groups. The outcomes of this study suggested that both additional fish oil supplementation and feeding frequency had positive impacts on tilapia growth, tissue energy storage and fatty acid profile. Although, indices like ammonia excretion and muscle protein deposition favored two times feeding frequency, additional oil notwithstanding that tilapia juveniles will perform well with elevated oil coated diet.